MARTYNAS JANKUS: CONTRIBUTION TO THE MUSICAL CULTURE OF LITHUANIA MINOR - KŠANIENĖ, DAIVA KŠANIENĖ (Knygotyra, 2015)
Martynas Jankus (1858–1946) was a cultural activist, printer, public speaker, member of the Aušra Society, and fighter for the rights of Lithuanians in Lithuania Minor, who earned the name of the patriarch of Lithuania Minor by his Lithuanian activities and made a great contribution to the musical culture of the region. M. Jankus left a lasting imprint in almost every field of the Lithuanian cultural-musical expression in Lithuania Minor. An advocate of national rebirth, a fighter against Germanization, M. Jankus was active in the establishment of Lithuanian cultural societies (frequently related to musical activity) and in the organization of their work in the late 19th – early 20th century. As soon as he turned 20, M. Jankus started collaborating with the German Society of Lithuanian Literature founded in Tilsit on October 14, 1879, and he worked alongside other cultural activists of Lithuania Great and Lithuania Minor. One can assume that Jankus participated in, or at least supported, most of the works of that society, including the publishing of significant monuments of musical culture of Lithuania Minor: a collection of Lithuanian folk songs with scores Dainų Balsai (‘Voices of Songs’) by Christian Bartsch (Volume 1 in 1887 and Volume 2 in 1889), as well as a collection of Lutheran hymns harmonized for a 4-voice-choir Giesmių balsai (‘Voices of Hymns’) (1894) by Woldemar Karl Theodor Hoffheinz. Even though M. Jankus’ activities in the Lithuanian Literature Society were reflected indirectly, he was one of the most active organizers and ideological leaders in establishing Lithuanian cultural societies in Lithuania Minor. Having failed to establish the intended society of Lithuanian science and education, the progressive Lithuanians of Lithuania Minor took resolute measures, as the time was ripe to have a Lithuanian society in Lithuania Minor. On February 15, 1885, Martynas Jankus, Jurgis Mikšas, Kristupas Voska and Ernst Weyer declared that they established the Lithuanian Society Birutė in Tilsit. Next to different cultural activities, the Birutė Society paid a great attention to the popularization of art via arrangement of Lithuanian festivals with performances, music, and songs. Chairmen of the Birutė Society changed frequently. In 1889–1892, it was chaired by M. Jankus. During his chairmanship, the 10th anniversary of the Society was approaching. It was also due to his efforts that, during the celebration of the aniversary, the first public concert of Lithuanian songs took place in Lithuania Minor, and it brought to the audience of the Lietuvninkai great surprise and joy. In the autumn of 1895, by the efforts of the leaders of the Society, the Birutė choir started to form. V. Storostas (Vydūnas), who at the time had begun to work with the Lithuanian choir of the Tilsit church, was invited as the leader of the Birutė choir. On February 16, 1896, during the festival of the Society, the choir performed several Lithuanian songs from V. Kudirka’s Kanklės collection at the Tilsit Riflemen’s Home. M. Jankus was deeply interested in the activities of Lithuanian choristers from the Birutė and Tilsit choirs and in their artistic plans, and frequently wrote reviews of different events. Among his manuscripts, a review of the performance of Vydūnas’ play Birutininkai ‘Members of the Birutė Society’ in 1910 was found. Thanks to the Birutininkai, including M. Jankus, starting with 1911, youth societies in different places of Lithuania Minor started forming. Since 1912, having got together into the Santara of Lithuanian societies, they held common and separate festivals with the compulsory presence of choirs. All the chorister societies followed the tradition of the Birutė and Tilsit Chorister Societies and regularly gave concerts in different places of the region. The major and permanent place of annual meetings and festivals of the societies, with M. Jankus as the soul of the events, was Rambynas Hill. M. Jankus supported the idea of the first Song Festival of the Lithuanians of Lithuania Minor in Klaipėda on June 6–7, 1927, and contributed to its preparation. The successful first Song Festival of the Lithuanians of Lithuania Minor, as well as the following ones in 1933 and 1938 in which Lithuanian songs alone were performed, met M. Jankus’ expectations cherished from his early youth. In those festivals, great attention was paid to the repertoire of songs and hymns of Lithuania Minor. For M. Jankus, the Lithuanian folk song was a spiritual treasure, the protector and carrier of Lithuanianness. He made every effort to revive the folk song. In the late 19th century, in his printer’s shop in Tilsit, next to other publications, he published collections of Lithuanian folk songs and of poems of Lithuanian poets performed as songs. The greatest merit of M. Jankus is his achievements in protecting, cherishing, and popularising the folk song and by that, setting his environment a good example. In his home, music and song enjoyed special attention. The song was the identity of M. Jankus, of his family and friends. M. Jankus, the great fosterer of Lithuanianness, advocate of Lithuanian music, was a connoisseur of Lithuanian folk songs; he knew a great number of them, performed them beautifully, and urged other people not to forget the songs of their own nation. All the family of M. Jankus were excellent singers. The surviving songs of M. Jankus, recorded both on paper and in musical records, form an especially valuable part of the musical heritage of the Lithuanians of Lithuania Minor. In the versatile social-cultural activities of M. Jankus, his merits to the musical culture of Lithuania Minor stand out especially distinctly.